The multiple temperature heater platforms for solder Electromigration test conducted at room temperature - Hou, Yuejin (2010)
To accommodate the increasing input-out (I/O) counts in future integrated circuits, the size of the solder bumps has to shrink and current density through each solder bump increasing. With the ever-increasing current density through the solder bumps, electromigration (EM) remains as a main concern for the reliability of future solder bumps. This phenomenon is responsible for the structural damage of solder bumps in the form of void formation caused by ionic diffusion driven by high electron wind force.